Noise-induced transition from periodic to chaotic synchronization in coupled limit cycle oscillators - Okumura, K.; Ichiki, A. (Europhysics letters, 2025)
A solvable model of noise effects on globally coupled limit cycle oscillators is proposed. These oscillators are subject to the influence of independent and additive white Gaussian noise. The averaged motion equation of the system with infinitely coupled oscillators is derived without any approximation through an analysis based on the nonlinear Fokker-Planck equation. It is demonstrated that with an increase in the noise intensity, a transition from periodic synchronization to chaotic synchronization occurs, which is associated with the emergence of macroscopic chaotic behavior.